2011
DOI: 10.1007/s00442-011-2127-5
|View full text |Cite
|
Sign up to set email alerts
|

Local versus regional intraspecific variability in regeneration traits

Abstract: Intraspecific trait variability has a fundamental contribution to the overall trait variability. However, little is known concerning the relative role of local (e.g. disturbances and species interaction) and regional (biogeographical) processes in generating this intraspecific trait variability. While biogeographical processes enhance plant trait variability between distant populations, in fire-prone ecosystems, recurrent fires may have a preponderant role in generating variability at a local scale. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…Poorter et al 2009). Species may therefore vary in which quantitative traits are stable across given gradients, so tests should be made before a trait is taken to be stable for a given species (Albert et al 2010(Albert et al , 2012Hulshof and Swenson 2010;Messier et al 2010;Moreira et al 2012).…”
Section: Selection Of Speciesmentioning
confidence: 99%
“…Poorter et al 2009). Species may therefore vary in which quantitative traits are stable across given gradients, so tests should be made before a trait is taken to be stable for a given species (Albert et al 2010(Albert et al , 2012Hulshof and Swenson 2010;Messier et al 2010;Moreira et al 2012).…”
Section: Selection Of Speciesmentioning
confidence: 99%
“…Within species, a review of studies comparing populations in sites with different precipitations found that low rainfall during seed development favours the occurrence of PY (Hudson et al 2015 and reference therein). In addition, some degree of intra-population variability has been observed in regeneration traits (Moreira et al 2012;. Particularly, studies that analysed PY variation within populations found important differences among individuals (Pérez-García 1997; Lacerda et al 2004;Masaka & Yamada 2009).…”
mentioning
confidence: 99%
“…Greater or lesser concentrations of some nutrients in the regrowing tissues occurs as a result of increased metabolic activity linked with the capacity of translocated nutrients from subterranean organs to above ground plant parts [59,60], which was observed in managed rosewood plantations.…”
Section: Changes In Nutritional Status Associated With the Managementmentioning
confidence: 99%
“…This is especially important for rosewood seedlings which, in the first year of cultivation, need to be protected from directly incident sunlight in order to avoid photosynthetic photoinhibition [64]. In contrast, weed control is rarely required during with coppicing and canopy closure is achieved quickly [60].…”
Section: Rosewood Shoots Following Above-ground Biomass Managementmentioning
confidence: 99%
See 1 more Smart Citation